Synthesis and Biological Evaluation of New Schiff Bases Derived from 4-Amino-5-(3-fluorophenyl)-1,2,4-triazole-3-thione - Sara Janowska; Dmytro Khylyuk; Michał Janowski; Urszula Kosikowska; Paulina Strzyga-Łach; Marta Struga; Monika Wujec (Molecules, 2023)
The treatment of infectious diseases is a challenging issue faced by the medical community. The emergence of drug-resistant strains of bacteria and fungi is a major concern. Researchers and medical professionals are working to develop new and innovative treatments for infectious diseases. Schiff bases are one a promising class of compounds. In this work, new derivatives were obtained of the 4-amino-5-(3-fluorophenyl)-2,4-dihydro-3H-1,2,4-triazole-3-thione reaction, with corresponding benzaldehydes with various substituents at position 4. The antibacterial and antifungal activities of all synthesized compounds were tested. Several new substances have shown moderate antifungal activity against Candida spp. The highest activity directed against C. albicans was shown by compound RO4, with a 4-methoxyphenyl moiety and an MIC value of 62.5 µg/mL. In order to check the toxicity of the synthesized compounds, their effect on cell lines was examined. Additionally, we tried to elucidate the mechanism of the antibacterial and antifungal activity of the tested compounds using molecular docking to topoisomerase IV, D-Alanyl-D-Alanine Ligase, and dihydrofolate reductase.